Hot deformation behaviors and dynamic softening mechanism of 6%Si high-silicon austenitic stainless steel - Yong Hu; Lihua Wang; Minghui Ouyang; Yongqi Hu; Cheng Chu (Journal of Materials Research and Technology, 2023)
The hot deformation behaviors and softening mechanism of 6%Si high-silicon austenitic stainless steel were investigated under deformation conditions of 1000–1200 °C/0.01–10 s−1. The constitutive equation was established based on the stress-strain curves, and the processing maps were drawn based on the Dynamic Material Model (DMM) at different strain levels. The results show that the activation energy(Q) of hot deformation is 368.555 kJ/mol. The peak region of the hot processing maps is 1130–1170 °C/0.01–0.03 s−1 at the strain of 0.7, the η value is 0.47, indicating that the best hot workability can be achieved in this region. At high strain rates (1000–1200 °C/0.66–10 s−1), the material is easily destabilized, while in the non-destabilized zone, η values are greater than 0.3, excluding the processing danger zone, and a better microstructure can be obtained. The accuracy of the processing maps established in this paper was verified by combining the microstructural morphology of different regions with the processing maps. Under the deformation conditions of 1200 °C/0.01 s−1, the χ phase and a small amount of δ ferrite are precipitated. The second phases induce the occurrence of a fracture along the grain while refining the grain size. Therefore, processing should be avoided in the range of second-phase precipitation. Crystallographic information analyses showed that the softening mechanism of high-silicon austenitic stainless steel is mainly discontinuous dynamic recrystallization (DDRX), and continuous dynamic recrystallization (CDRX) occurs in the softening mechanism between 1100 and 1150 °C.